ANALISIS HUKUM TERHADAP PERLINDUNGAN KONSUMEN PRODUK PASAR MODAL DI INDONESIA - Hamzah Hamzah (Fakultas Hukum Universitas Kristen Indonesia, 2015)
Abstract Consumer protection is an important issue in commercial domain. Consumer goods and services should have been protected. The most known is consumer goods protection. This article deals with consumer securities protection. Consumer securities protection has been applied in United States due to financial crisis, including fraud. Indonesia has experienced one of tremendous financial fraud in Bank Century-Antaboga. The case shows that separated surveillence on financial industry has weakness, instead of the integration of financial industry. The role of authority is influential in governing banking-securities industry. In Bank Century-Antaboga case give us a factual absence of disclosure in offering and selling the securities instrument. Otoritas Jasa Keuangan (OJK) should play its role to the application of disclosure principle, otherwise the Bank Century- Antaboga case will occur again. Kata Kunci: Perlindungan Konsumen, Produk Pasar Modal, Otoritas